Lingering with Multispecies Kin: Re-Turning to Encounters between Children, Invertebrates and Amphibians - Jenny Byman; Kristiina Kumpulainen; Jenny Renlund (Australian Journal of Environmental Education)
Based on an ethnographic study in a Finnish primary school, we explored lingering as both a pedagogical approach and a methodological concept for multispecies education research and practice. Through this conceptual thinking, we “re-turned” to the multiplicities that unfolded from noticing rhythms, enterings and different lifeworlds to show how children’s lingering encounters developed into speculative inquiries about how invertebrates and amphibians generate polyphonous affects and temporalities. In our study, children’s “attuning-with” clay, waste materials, photographs, and stop-motion animation opened up the unfamiliar worlds and temporalities of invertebrates and amphibians, involving active silences, slow rhythms, and awkward becomings. Overall, the study highlights that children’s attuning-with the uncertainties of today’s socioecological world create new avenues for thinking about multispecies relationalities.